Addressing Challenges and Enhancing Regional Economic Competitiveness through Regional Cooperation - Suyanto; Ryan Firdiansyah Suryawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study discusses strategies for overcoming challenges and increasing economic competitiveness in a region through regional cooperation. We identify several challenges that may arise in carrying out regional cooperation, such as differences in interests, regulatory barriers, and cultural differences. However, with the right strategy, these challenges can be overcome and generate long-term benefits for the region. This research also discusses important enabling factors in regional cooperation, including political commitment, coordination between local governments, and private sector participation. In addition, we provide policy recommendations and concrete action steps that can be taken by the government and related stakeholders to increase regional economic competitiveness through regional cooperation. In conclusion, this study emphasizes the importance of regional cooperation in overcoming regional economic challenges and increasing competitiveness. Through strong regional collaborations, regions can optimize their economic potential and achieve sustainable growth.